1987
DOI: 10.1172/jci112899
|View full text |Cite
|
Sign up to set email alerts
|

Safety, infectivity, immunogenicity, and in vivo stability of two attenuated auxotrophic mutant strains of Salmonella typhi, 541Ty and 543Ty, as live oral vaccines in humans.

Abstract: Two Salmonella typhi mutants, 541Ty (Vi+) and 543Ty (Vi-)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(84 citation statements)
references
References 52 publications
0
84
0
Order By: Relevance
“…This vaccine has been extensively used to immunize both adults and children. 23,24 In contrast to laboratory conditions, the clinical application of the available viral vectors has shown that the extent of gene transfer and expression levels are generally low. 25 These shortcomings mean that high doses of viral vectors or lipid/DNA complexes are usually required to achieve a measurable gene transfer in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine has been extensively used to immunize both adults and children. 23,24 In contrast to laboratory conditions, the clinical application of the available viral vectors has shown that the extent of gene transfer and expression levels are generally low. 25 These shortcomings mean that high doses of viral vectors or lipid/DNA complexes are usually required to achieve a measurable gene transfer in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the WHO has given a high priority to the improvement of vaccines against Salmonella typhi in an effort to attain greater control over the disease (60). The development of a safe but highly immunogenic live oral typhoid vaccine for use in such programs will have advantages over the currently available reactogenic wholecell parenteral typhoid vaccines and the well tolerated but modestly immunogenic live oral vaccine strain Ty21a (31,61,62). Salmonella typhi penetrates the gastrointestinal epithelial barrier and infects phagocytes mainly macrophages within the lamina propia where they adapt to prolonged survival thereby giving the bacteria an opportunity to spread to other systemic organs.…”
Section: Salmonella: a Vaccine Vectormentioning
confidence: 99%
“…A significant rise in antibody level (seroconversion) was defined as a net increase of 0.15 00 units above preimmunization values [7].…”
Section: Safety and Immunogenicity Of Salmonella Typhi Ty21amentioning
confidence: 99%
“…Fully 37% of children (63/170) had elevated baseline antibody levels (00~0.75, based on levels in North American volunteers who ingested S. typhi in vaccine challenge studies), suggesting prior exposure to S. typhi or another group 0 Salmonel/a species [7]. Of this subgroup, 89% of those who received vaccine seroconverted (31/35), while only 39%ofplacebo recipients did so (11/28; P < .005).…”
Section: Safety and Immunogenicity Of Salmonella Typhi Ty21amentioning
confidence: 99%